Yearbook of fisheries statistics. - Food and Agriculture Organization of the United Nations; Food and Agriculture Organization of the United Nations. Fisheries Division; Food and Agriculture Organization of the United Nations. Fisheries Division. Economics and Statistics Branch (Washington, D.C. Food and Agriculture Organization of the United Nations, 1947)
Annual
Prepared 1947- by the Fisheries Division of the Food and Agricultural Organization of the United Nations.
Keywords: Fisheries -- Statistics -- Periodicals